Developing Soil Conservation Strategies with Technical and Community Knowledge in a Degrading Sub‐Humid Mountainous Landscape. (16th May 2017) - Guzman, Christian D.; Tilahun, Seifu A.; Dagnew, Desslegn C.; Zegeye, Assefa D.; Yitaferu, Birru; Kay, Robert W.; Steenhuis, Tammo S.
Abstract: Worldwide, soil erosion has greatly decreased agricultural productivity and continues unabatedly despite decades of developing sustainability and soil conservation strategies. Current strategies need integrated interdisciplinary perspectives to develop more effective measures, especially in degrading mountainous landscapes where rising sediment concentrations persist. By comparing spatio‐temporal field observations and community perceptions with the Geographic Information System (GIS)‐based universal soil loss equation (USLE), this study critically examined theorized erosion patterns (by USLE) in a degraded landscape (Shanko Bahir, Ethiopia) to improve soil conservation strategy development. Daily hydro‐sedimentological data (showing 792 mm of rainfall leading to 3·2 Mg ha −1  y −1 of sediment yield) revealed mild but variable erosion patterns in 2012. Overlooking hydrology hindered the USLE's suitability for conservation planning. For instance, the median infiltration rate (33 mm h −1 ) was rarely exceeded (3·5% of events), meaning runoff‐induced erosion risk were not well predicted spatio‐temporally by the USLE R‐factor. Conversely, heterogeneous local perspectives explicitly considered accumulated runoff, saturation ("the water at the top level rests on the bottom"), fertility, and gullies as drivers of erosion ("black soil breaks and forms gorges"). Additionally, they designated steeper mono‐cropped lands as at risk (incidentally also highlighted by USLE). Observational evidence showed steeper midslope areas decreasing in topsoil depth by 14 mm, flatter downslope areas by 0·8 mm, and the mild upslope areas increasing 2 mm. Operationalizing effective soil conservation strategies will require expanding beyond (USLE‐based) technical knowledge to incorporate local stakeholders and consider the main hydrological processes causing erosion in sub‐humid mountainous landscapes: saturated pathways, downslope saturation, subsurface flow, and gully formation. Copyright © 2017 John Wiley & Sons, Ltd.